Possible evidence for contribution of arbuscular mycorrhizal fungi (AMF) in phytoremediation of iron-cyanide (Fe-CN) complexes - Sut, Magdalena (Ecotoxicology (London, England), 2016)
Arbuscular mycorrhizal fungi (AMF) are integral functioning parts of plant root systems and are widely recognized for enhancing contaminants uptake and metabolism on severely disturbed sites. However, the patterns of their influence on the phytoremediation of iron-cyanide (Fe-CN) complexes are unknown. Fe-CN complexes are of great common interest, as iron is one of the most abundant element in soil and water. Effect of ryegrass (Lolium perenne L.) roots inoculation, using mycorrhizal fungi (Rhizophagus irregularis and a mixture of R. irregularis, Funneliformis mosseae, Rhizophagus aggregatus, and Claroideoglomus etunicatum), on iron-cyanide sorption was studied. Results indicated significantly higher colonization of R. irregularis than the mixture of AMF species on ryegrass roots. Series of batch experiments using potassium hexacyanoferrate (II) solutions, in varying concentrations revealed significantly higher reduction of total CN and free CN content in the mycorrhizal roots, indicating greater cyanide decrease in the treatment inoculated with R. irregularis. Our study is a first indication of the possible positive contribution of AM fungi on the phytoremediation of iron-cyanide complexes